2023
DOI: 10.3847/2041-8213/acd457
|View full text |Cite
|
Sign up to set email alerts
|

An Extremely Compact, Low-mass Galaxy on its Way to Quiescence at z = 5.2

Abstract: We report the discovery of a low-mass z = 5.200 ± 0.002 galaxy that is in the process of ceasing its star formation. The galaxy, MACS0417-z5BBG, is multiply imaged with magnification factors ∼40 by the galaxy cluster MACS J0417.5-1154, observed as part of the CAnadian NIRISS Unbiased Cluster Survey (CANUCS). Using observations of MACS0417-z5BBG with a JWST/NIRSpec Prism spectrum and NIRCam imaging, we investigate the mechanism responsible for the cessation of star formation of the galaxy and speculate about po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…Thanks to JWST we can now study them and investigate the role of the various feedback processes in their evolution. Looser et al (2023) recently reported the discovery of a quiescent low-mass galaxy at redshift z = 7.3 (see also Strait et al 2023 for another very low-mass quiescent system at z = 5.2) from the JADES program, JADES-GS-z7-01-QU. Following this work, we define as quiescent those galaxies with no (or negligible) star formation activity at the epoch of observation.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to JWST we can now study them and investigate the role of the various feedback processes in their evolution. Looser et al (2023) recently reported the discovery of a quiescent low-mass galaxy at redshift z = 7.3 (see also Strait et al 2023 for another very low-mass quiescent system at z = 5.2) from the JADES program, JADES-GS-z7-01-QU. Following this work, we define as quiescent those galaxies with no (or negligible) star formation activity at the epoch of observation.…”
Section: Introductionmentioning
confidence: 99%
“…It shows properties that are consistent with other galaxies detected with JWST (e.g., Bunker et al 2023;Topping et al 2023); however, its true nature was only revealed through resolved SED fitting. While strong Balmer breaks can be present at high redshift, they are rare (Endsley et al 2023b;Laporte et al 2023;Looser et al 2023;Strait et al 2023). With the newest data for MACS1149-JD1, a strong Balmer break is excluded.…”
Section: Discussionmentioning
confidence: 99%
“…MACS0417-z5BBG is a z = 5.2 lensed galaxy observed by Strait et al (2023); it has a low stellar mass, M å = 4.3 × 10 7 M e . Just like JADES-GS-z7-01-QU, it exhibits a recent sudden SF drop, likely leading to a quiescent phase.…”
Section: Interpreting Macs0417-z5bbgmentioning
confidence: 99%
“…Just like JADES-GS-z7-01-QU, it exhibits a recent sudden SF drop, likely leading to a quiescent phase. Considering the SED fitting from Strait et al (2023), the (Leitherer et al 1999). Right: cooling functions (Λ) in the interstellar medium as a function of temperature (T vir ) derived with KROME (Grassi et al 2014).…”
Section: Interpreting Macs0417-z5bbgmentioning
confidence: 99%
See 1 more Smart Citation